1971
DOI: 10.1021/jo00819a021
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemistry of natural products. II. Electrolytic oxidation of some simple 1,2,3,4-tetrahydroisoquinoline phenols

Abstract: A series of derivatives of 1,2,3,4-tetrahydroisoquinoline has been oxidized electrolytically. Those containing phenol groups were dimerized to yield carbon-carbon dimers and carbon-oxygen-carbon dimers. Some of the variables such as the nature of the anode, the cell design, the solvent, the pH, and the reaction time were considered. The optimum conditions for the coupling of these phenols would seem to be oxidation of their sodium salts in CHsCN using tetraethylammonium perchlorate as supporting electrolyte an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

1978
1978
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 3 publications
0
17
0
1
Order By: Relevance
“…Both systems have been used for the oxidative coupling of corypalline (7-hydroxy-6-methoxy-Nmethyl-l,2,3,4-tetrahydroisoquinoline) and related compounds in aqueous media, with yields comparable to those obtained at graphite cloth or graphite felt electrodes (7). In particular, the simplicity of construction of the GBC and the ease with which its paste layer can be renewed make this system potentially useful for general oxidative syntheses.…”
Section: Resultsmentioning
confidence: 99%
“…Both systems have been used for the oxidative coupling of corypalline (7-hydroxy-6-methoxy-Nmethyl-l,2,3,4-tetrahydroisoquinoline) and related compounds in aqueous media, with yields comparable to those obtained at graphite cloth or graphite felt electrodes (7). In particular, the simplicity of construction of the GBC and the ease with which its paste layer can be renewed make this system potentially useful for general oxidative syntheses.…”
Section: Resultsmentioning
confidence: 99%
“…Another possible concerted reaction was observed in a study of the dimerization of simple phenolic tetrahydroisoquinolines (64). When the anion of N-methyl-6-methoxy-7-hydroxy-1,2,3,4-Downloaded by COLUMBIA UNIV on December 9, 2014 | http://pubs.acs.org Publication Date: January 1, 1989 | doi: 10.1021/bk-1989-0390.ch014 tetrahydrcisoquinoline, 68, was oxidized, a carbon-carbon dimer, 69 was isolated in 85 % yield.…”
Section: Unique Surface Chemistry Observed From Natural Product Studiesmentioning
confidence: 87%
“…[539][540][541][542][543] Seminal work on the intermolecular anodic oxidative coupling of phenols demonstrated that corypalline (210) could be electrochemically oxidized to the corresponding dimer (211, Scheme 63). [544][545][546][547][548] However, attempts to carry out the related intramolecular C-C coupling on laudanosine (212) resulted in oxidative dearomatization of one of the phenolic moieties and furnished O-methylflavinantine (213, Scheme 64). [549][550][551][552][553] Similar reactivity has also been observed for the related alkaloids amurine, oxocrinine, oxomaritidine and pallidine.…”
Section: Electrochemical Oxidative Cross-couplingsmentioning
confidence: 99%